Metallicity gradients in intermediate-redshift absorption-selected galaxies. Issue Volume 14:Issue A30(2018) (August 2018) - Christensen, Lise; Rhodin, Henrik; Møller, Palle
Abstract: . Metallicity gradients are most frequently investigated directly from galaxies observed in emission. We have shown that galaxies detected via strong quasar absorption lines also exhibits a metallicity gradient in the outskirts and circumgalactic medium out to 40 kpc distance. We infer a metallicity gradient of −0.022 dex kpc −1 for absorption-selected systems at redshifts 0.1 z 3. Applying this metallicity gradient and a flattening of the gradient beyond 12 kpc, we demonstrate that absorption-selected galaxies obey the same mass-metallicity relation (MZR) as observed for luminosity-selected galaxies.